Description of Knowledge of Third Trimester Pregnant Women About Danger Signs of Pregnancy at Panjang Health Center, Bandar Lampung in 2023 - Ika Fitria Elmeida; Nurlaila; Nurchairina (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to: 1) Identify the knowledge of third trimester pregnant women about the danger signs of pregnancy based on age. 2) Identify the knowledge of third trimester pregnant women about the danger signs of pregnancy based on education. 3) Identify the knowledge of third trimester pregnant women about the danger signs of pregnancy based on work. This research uses a descriptive cross sectional research design. The population in this study were all pregnant women in the third trimester who had their pregnancies checked in February - August 2023 at the Panjang Community Health Center. Bandar Lampung City. The sample in this research is the entire population used as a sample. The instrument used in this research was a questionnaire. The results of this research show: 1). Third trimester pregnant women's knowledge of the danger signs of pregnancy based on age, most of those of healthy reproductive age (20-35 years) have good knowledge. 2). Third trimester pregnant women's knowledge about the danger signs of pregnancy is based on education, most of them have good secondary education. 3). Third trimester pregnant women's knowledge about the danger signs of pregnancy is based on work, most respondents who work have good knowledge. The conclusion of this research is that the mother's age, education and occupation influence pregnant women's knowledge about the danger signs of TM III pregnancy.